Peningkatan Kesejahteraan Masyarakat melalui Pemberdayaan Ekonomi Berbasis Potensi Lokal di Desa Oemasi, Kecamatan Nekamese, Kabupaten Kupang - Yohanes Made Supadi; Yolanda Odilia Maria Widyasari; Markus Asa; Thomas Ola Langoday (Jurnal Pengabdian Masyarakat, 2026)
Improving rural community welfare remains a significant challenge, particularly due to the underutilization of local potential, limited entrepreneurial skills, and restricted market access. This condition is also found in Oemasi Village, Nekamese District, Kupang Regency, where communities tend to manage resources traditionally without optimal added value. This community service aims to enhance community welfare through local potential-based economic empowerment. The method used is a participatory approach involving stages of needs identification, entrepreneurship training, product processing practices, business mentoring, and evaluation. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative methods. The results indicate a significant improvement in entrepreneurial knowledge, product processing skills, and community motivation to develop businesses. Additionally, the community has begun to optimize local resources into value-added products and expand market access. This activity also encourages economic independence and strengthens local business institutions at the village level. Therefore, local potential-based economic empowerment is proven to be an effective strategy in improving sustainable community welfare.